Rock mass classification and geo-resistivity properties of granite from Pahang, Malaysia - Ahmad Faiz, Salmanfarsi; Haryati, Awang (Penerbit UMP, 2025)
In tropical climate, exposed rocks are significantly weathered to form extensive weathering profile, which greatly affect the engineering integrity of the material. Geophysical method such as the electrical resistivity mapping have increasingly being used in the classification of the geoengineering properties of rock slope alongside conventional field and laboratory testing. In this study, comprehensive assessment of the weathered granite are carried out on selected exposed granite slopes in the Karak-Lanchang area, Pahang. Petrological analysis indicated quartz minerals as being the most stable mineral among the weathering grade. With increasing weathering grade, for physical properties of the granite of porosity and moisture content shows positive trend, whereas the specific gravity, slake durability index, and ultrasonic pulse velocity shows negative trend; for mechanical properties, the surface hardness rebound value, point load strength, and uniaxial compressive strength shows negative trend with increase of weathering grade. Mapping from the resistivity zones correlate with five zones of weathering grade, ranging from <200Ωm for Grade V and up to 3000Ωm for Grade I. The electrical resistivity value would also correspond to the different engineering properties of the weathered granite. Engineering properties results indicate the mechanical behaviour of high durability to very high durability and medium strength to very high strength of the rock material. Rock mass rating of the slopes fall under Class II (‘good’). The results from electrical resistivity mapping, engineering tests, and rock mass classification indicate the slopes to be intact. From the results, a general geo-engineering properties of weathered granite is proposed